Manufacture of automotive component using reverse engineering and manufacturing additive techniques / Mohamad Irwan Yahaya... [et al.] - Yahaya, Mohamad Irwan; Samsuddin, Zulhelmi; Mohd Rodzi, Ana Syahidah; Hemdi, Abd. Rahman; Othman, Muhamad; Mohamed Noor, Rizal (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
Reverse engineering is an extraction process of design data from an existing product in order to get its 3D model by data acquisition method. This type of engineering is often applied in software engineering, biomedical field, and parts restoration. The main reasons for implementing reverse engineering are due to obsolete parts, unavailable spare parts and the absence of documentation design.. The objective of the work is to reproduce an automotive part utilizing a 3D printer from data acquisition and CAD model. The reverse engineering technique in this work involves data acquisition, surface and model construction, post-processing and fabrication of the final product. One of the equipment in the non-contact method, the 3D scanner is used to extract design data from the master part. Then, the scanned model is transferred to Solidworks in order to reconstruct the missing features in the model. The findings show that the reverse engineering technique used in this work can reproduce the automative part which is near net-shape of the master part. However, the CAD model require some surface and model reconstruction due to data loss during the conversion of information from scanning data to CAD data. After the final product is fabricated using a 3D printer, it is compared with the master part in terms of the difference of dimensions found between them. Besides, the data loss occurred throughout data acquisition is also discussed in this work. As a conclusion, reverse engineering should be the best alternative to reproduce an object without any design details provided.